Penguatan Literasi Digital untuk Meningkatkan Kreativitas dan Budaya Pembelajaran Peserta Didik - Dwi Harianti; Aprilia Azzahra; Auliaul Hanifa; Jaesi Ora Pau; Lisda Fauziyah; Muhamad Nursan Irmansyah; Siti Zubaidah; Yulita Puji Lestari (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2026)
Advances in digital technology in the field of education require students to possess digital literacy skills that are not merely technical but also encompass critical thinking, creativity, communication, and the productive use of technology. However, students still tend to use technology primarily for entertainment rather than to support the learning process. This community service activity aims to improve digital literacy, creativity, and the learning culture of students at SMP Negeri 7 in South Tangerang City through an educational and participatory approach. The activity was implemented through initial observation, digital literacy awareness sessions, training in the use of educational digital media, practice in creating digital-based creative works, and evaluation of the activity via pre- and post-tests. The results of the activity indicate that students demonstrated improved understanding of digital literacy, digital ethics, the use of educational digital media, and active engagement in technology-based learning. In addition, students are able to produce various simple digital works, such as educational posters and presentation materials using digital applications. This initiative also fosters a learning culture that is more collaborative, creative, and adaptable to advancements in digital technology. Thus, strengthening digital literacy can serve as an effective strategy for improving the quality of learning and developing students’ competencies in the digital age.